Analysis of pig iron desulfurization with mixtures from the CaO-Fluorspar and CaO-Sodalite system with the use of computational thermodynamics - Grillo,Felipe Fardin (2013)
This work aims at the use of computational thermodynamics in the study of desulfurization of pig iron through CaO-Fluorspar and CaO-Sodalite mixtures. Experiments were performed with the addition of different mixtures from these systems in molten pig iron at a temperature of 1,400ºC. The test results were analyzed and compared with those obtained by the computational thermodynamics software program THERMOCALC. Through this software, were calculated the equilibrium sulfur content in the metal, solid phases, and the amount of liquid in each desulfurizing mixture used in the process at a temperature of 1,400ºC. The computational thermodynamics proved to be an effective tool in predicting the desulfurization capacity of the mixtures.